Template Synthesis of Hybrid Schiff Base Complexes of Zn2+, Cd2+, and Hg2+ Ions - Abdul-Razak H. Al-Sudani (Journal of Global Pharma Technology, 2019)
Five Schiff base complexes of d10 metals were prepared via Template synthesis procedure. This procedure included the synthesis and isolation of intermediate diamine complexes derived from N,N-Diethylethylenediamine; (Et2ne), and appropriate metal salt; MCl2; (M= Zn2+, Cd2+, and Hg2+), followed by the condensation of either of Ortho-phathaldehyde (OPA) or Benzaldehyde with different intermediate diamine complexes of aforementioned metal ions. Moreover, the condensation reaction of the intermediate diamine complexes of the formula [HgCl2 (Et2ne) 2] with OPA failed to produce either the corresponding Schiff base – Mercury- or Organo - Mercury Complex. The identification of the reported Schiff base Metal complexes were  based on Elemental Analyses, Atomic Absorption; FT-IR, Vis-UV; and Molar Conductance. In addition to those techniques, 1H NMR and Mass Spec. were recorded for a couple of the reported complexes.Keywords: Template synthesis, Hybride Schiff Base, Schiff base-d10 metal complexes, Reduction of mercury diamine complex, N,N-Diethylethylenediamine,  Benzaldehyde, o- Phathaldehyde.